An Accurate In Vitro Model of the E. coli Envelope. (1st September 2015) - Clifton, Luke A.; Holt, Stephen A.; Hughes, Arwel V.; Daulton, Emma L.; Arunmanee, Wanatchaporn; Heinrich, Frank; Khalid, Syma; Jefferies, Damien; Charlton, Timothy R.; Webster, John R. P.; Kinane, Christian J.; Lakey, Jeremy H.
Abstract Gram‐negative bacteria are an increasingly serious source of antibiotic‐resistant infections, partly owing to their characteristic protective envelope. This complex, 20 nm thick barrier includes a highly impermeable, asymmetric bilayer outer membrane (OM), which plays a pivotal role in resisting antibacterial chemotherapy. Nevertheless, the OM molecular structure and its dynamics are poorly understood because the structure is difficult to recreate or study in vitro. The successful formation and characterization of a fully asymmetric model envelope using Langmuir–Blodgett and Langmuir–Schaefer methods is now reported. Neutron reflectivity and isotopic labeling confirmed the expected structure and asymmetry and showed that experiments with antibacterial proteins reproduced published in vivo behavior. By closely recreating natural OM behavior, this model provides a much needed robust system for antibiotic development.